2000
DOI: 10.1080/00288330.2000.9516926
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerances of two stream invertebrates exposed to diumally varying temperature

Abstract: For two key New Zealand freshwater invertebrates (the mayfly Deleatidium autumnale and the snail Potamopyrgus antipodarum) the upper thermal tolerances were measured in the laboratory under both constant and diumally varying temperatures. At constant temperature 50% mortality in 96 h ( const LT 50 ) occurred at 24.2 ± 0.9°C for mayflies and 31.0 ± 0.6°C for snails: values similar to previously published estimates (Quinn et al. 1994). For diurnally varying temperatures (daily amplitude 10°C) 50% mortality occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 12 publications
2
38
0
2
Order By: Relevance
“…Extreme Tw can stress or ultimately prove lethal to biota (e.g. Dallas & Rivers-Moore 2012; Martins et al 2011) although some fauna can deploy avoidance strategies and/or acclimate to high temperatures (Breau et al 2011;Cox & Rutherford, 2000;Geist et al 2011). Nonetheless, sub-lethal Tw can still impact on spawning and breeding, hatching, growth, behaviour, distribution and phenology, thereby altering population structure and dynamics (Durance and Ormerod, 2007;Thackeray et al 2010;Ward & Stanford 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme Tw can stress or ultimately prove lethal to biota (e.g. Dallas & Rivers-Moore 2012; Martins et al 2011) although some fauna can deploy avoidance strategies and/or acclimate to high temperatures (Breau et al 2011;Cox & Rutherford, 2000;Geist et al 2011). Nonetheless, sub-lethal Tw can still impact on spawning and breeding, hatching, growth, behaviour, distribution and phenology, thereby altering population structure and dynamics (Durance and Ormerod, 2007;Thackeray et al 2010;Ward & Stanford 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Mayflies are one of the most widespread groups of aquatic invertebrates and are amongst the most sensitive to anthropogenic disturbance (Ward 1992; Hickey 2000; Maxted et al 2000;Collier 2002). Several studies have reported adverse responses among mayfly species to high water temperature (e.g., Quinn et al 1994;Cox & Rutherford 2000;Chadwick & Feminella 2001), low dissolved oxygen (e.g., Nebeker 1972), and increased levels of sediment (e.g., Ciborowski et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed below, there is evidence that this assumption may not be valid, especially for Potamopyrgous. Cox & Rutherford (2000) conducted a set of experiments in winter (April-June) 1998 in which animals were collected from two spring-fed streams (daily mean natural temperature 11-13°C) and acclimated for 24-h at 15-16°C. Test animals (30 per experiment) were then transferred to a high temperature bath, temperature was held constant for 96 h, and the number of live animals (A,) was measured after t = 24, 48, 72, and 96 h (all experiments) and 4, 14, 40, and 66 h (some experiments).…”
Section: Methodsmentioning
confidence: 99%
“…In their winter experiments Cox & Rutherford (2000) also exposed test animals to diurnally varying (±5°C) temperature using the same methods described above. It should be noted that the results of these diurnally varying temperature experiments were not used during model calibration.…”
Section: Model Testingmentioning
confidence: 99%
See 1 more Smart Citation